(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Chronic pericarditis is inflammation of the pericardium (the flexible 2-layered sac that envelops the heart) that begins gradually, is long-lasting, and results in fluid accumulation in the pericardial space or thickening of the pericardium. Sharp pain in your chest and back of the shoulders that feel better when you sit up and lean forward, and chest pain with breathing are two major clues that you may have pericarditis and not a heart attack.